2015
DOI: 10.3171/2014.9.spine14554
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following surgical intervention for impending and gross instability caused by multiple myeloma in the spinal column

Abstract: OBJECT Multiple myeloma is the most common primary tumor of the spine and is the most common primary malignant tumor of bone. Although spinal myeloma is classically a radiosensitive lesion, clinical or radiographic signs of instability merit surgical intervention. The authors present the epidemiology, surgical indications, and outcome data of a series of consecutive cases involving 31 surgically treated patients with diagnoses of multiple myeloma and plasmacytoma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…1,13,14,16,17,26,27,30,31,38,63,93,[95][96][97][98] However, surgical approaches to spinal tumors often necessitate extensive reconstruction of the spinal column and may require adjuvant chemotherapy or radiation; therefore, perioperative complication rates after spinal tumor surgery are higher than in other spinal operations. [34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, …”
mentioning
confidence: 99%
“…1,13,14,16,17,26,27,30,31,38,63,93,[95][96][97][98] However, surgical approaches to spinal tumors often necessitate extensive reconstruction of the spinal column and may require adjuvant chemotherapy or radiation; therefore, perioperative complication rates after spinal tumor surgery are higher than in other spinal operations. [34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, …”
mentioning
confidence: 99%
“…Spine surgery in this population has been shown to have the potential to improve patient outcomes,[2132053] but choosing the appropriate patient to take to surgery remains difficult given how current prognostic scores inaccurately estimate survival. [1333453]…”
Section: Discussionmentioning
confidence: 99%
“…[49444851] A randomized control trial of patients with metastatic spinal cancer with epidural compression showed that the surgical treatment is superior to radiotherapy alone;[38] the efficacy of surgery has been confirmed independently in the myeloma literature. [2132053] Spinal metastasis scoring systems have been developed[17304950] due to an increasing focus on the outcomes after metastatic surgery,[67243141] however, they have consistently underestimated overall survival (OS) in patients with MM. [1333453] Consequently, surgical decision making for this population is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier reports, the overall survival time in metastatic bone disease ranged between 6 and 22 months (28,29), depending on the type of primary tumor. Recent studies concluded that the median survival time of MM patients is longer as compared with that of patients with bone metastases (24,30). This explains the fact that, in myeloma patients requiring orthopedic surgery, a treatment decision should be made comprising a stable reconstruction of the bone defects.…”
Section: Discussionmentioning
confidence: 99%